Interferensi Sintaksis Bahasa Ibu terhadap Keterampilan Berbicara Bahasa Arab (Studi Kasus Mahasiswa Pendidikan Bahasa Arab STAI Syaichona Moh. Cholil Bangkalan) - Siti Maisaroh (STAI Syaichona Moh. Cholil Bangkalan, 2018)
Arabic is the second language that has to be learned in formal education institution and also becomes compulsory subject for students of Arabic department. Each language has different elements that make the students are difficult to master foreign language (Arabic). Moreover, language mastery must have four language skills where composition is one of skills in language. This article explains the result of the research concerns with the Indonesian language syntactical interference on Arabic speaking. Based on the result of the research, the ability of speaking or Arabic conversation still influenced by Indonesian language, even thought many students are able to speak with the appropriate grammar (nahwu and shorof) especially for the students of Arabic Department of Syaichona Moh. Cholil State Institute of Islamic Studies Bangkalan.